2021
DOI: 10.1101/2021.05.13.443927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Genome-Scale TF-DNA Interaction Network of Transcriptional Regulation of Arabidopsis Primary and Specialized Metabolism

Abstract: In single-celled microbes, transcriptional regulation by single transcription factors is sufficient to shift primary metabolism. Corresponding genome-level transcriptional regulatory maps of metabolism reveal the underlying design principles responsible for these shifts as a model in which master regulators largely coordinate specific metabolic pathways. Relative to individual microbes, plant metabolism is more complex. Primary and specialized metabolism occur within innumerable cell types, and their reactions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…We found spatially distinctive distribution patterns of several classes of TCA biosynthesis genes (Fig. 3a), which match localization signatures identified in a separate study of Arabidopsis roots 8 . In particular, ACONITASE ( ACO ) and SUCCINATE-COENZYME A LIGASE ( SCL ) gene expression levels in Arabidopsis correlated with the metabolite distributions observed in maize roots, suggesting that the developmental distribution of TCA metabolites is conserved across evolutionarily divergent plants.…”
Section: Mainsupporting
confidence: 85%
See 1 more Smart Citation
“…We found spatially distinctive distribution patterns of several classes of TCA biosynthesis genes (Fig. 3a), which match localization signatures identified in a separate study of Arabidopsis roots 8 . In particular, ACONITASE ( ACO ) and SUCCINATE-COENZYME A LIGASE ( SCL ) gene expression levels in Arabidopsis correlated with the metabolite distributions observed in maize roots, suggesting that the developmental distribution of TCA metabolites is conserved across evolutionarily divergent plants.…”
Section: Mainsupporting
confidence: 85%
“…Between 20 to 30 small molecules were localized per each developmental zone (Supplementary Figs. [8][9][10]. We hypothesized that these enrichment patterns might predict developmental functions.…”
mentioning
confidence: 99%
“…Depending on the regulatory stetting, a single regulatory interaction can be beneficial or detrimental for the system stability. Further, although a vast amount of data and information is available on regulatory interplay between genes, proteins metabolites, e.g., provided by genome-scale metabolic networks (Tang et al, 2021), many regulatory and metabolic interactions can be assumed to remain elusive or unknown. Affirmatively, even in long studied and well-known biochemical reaction networks, new reactions or regulatory interactions are still being discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning can be also used to infer gene regulatory networks. For example, a study showed that plant metabolism is transcriptionally coordinated via developmental and stress conditional processes 10 . Another approach, named EXPLICIT (Expression Prediction via Log- linear Combination of Transcription Factors), correctly predicted gene expression patterns from transcription factor information.…”
Section: Introductionmentioning
confidence: 99%